Analyse des effets de l’assurance et de la relation de confiance consommateur-producteur sur les possibilités d’abus des chirurgiens - Dionne, Georges (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractThe object of this paper is to analyse the effects of insurance and of the relation of trust between consumer and producer on the possibilities of fraud by the producer. Fraud is defined as the provision of unnecessary services to a consumer who does not possess full information about the quality of his purchase. The possibilities of fraud increase with insurance. In particular, they are very high with full insurance since real cost of search tends to infinite. Also we verify that good trust between consumer and producer limits search activities. We apply this model to the market of surgeons in the United States. This market reflects the main characteristics of the model: the consumer is not well informed, the relation of trust is important, the cost of search is high, the service is largely insured and there is excess capacity.